Structure of Co-65,Co-67 studied through the beta decay of Fe-65,Fe-67 and a deep- inelastic reaction - Pauwels, D; Ivanov, O; Bree, N; Buescher, J; Cocolios, T; Huyse, M; Kudryavtsev, Y; Raabe, R; Sawicka, M; Van de Walle, J; Van Duppen, P; Korgul, A; et al. (American Physical Society, 2009)
The neutron-rich isotopes Fe65,67 and Co65 have been produced at the LISOL facility, Louvain-La-Neuve, in the proton-induced fission of U238. Beams of these isotopes have been extracted with high selectivity by means of resonant laser ionization combined with mass separation. Yrast and near-yrast levels of Co65 have also been populated in the Ni64+U238 reaction at Argonne National Laboratory. The level structure of Co65 could be investigated by combining all the information from both the Fe65 and Co65β decay and the deep-inelastic reaction. The Fe65, Co65, and Fe67 decay schemes and the Co65 yrast structure are fully established. The Co65,67 level structures can be interpreted as resulting from the coexistence of core-coupled states with levels based on a low-energy proton-intruder configuration. © 2009 The American Physical Society.